Relationship between the ideal and reality in civil service: retrospective approach towards ethical problems in the interwar Lithuanian Republic - Jolanta Palidauskaitė (Lietuvos Istorijos Studijos)
The purpose of this study was to analyze the relationship between the ideal and reality in the First Lithuanian Republic when the foundations of contemporary Lithuanian civil service were laid down. Various scientists and Lithuanian legislators were involved in the construction of the ideal of civil service, but the reality and the image of the reality in media were different. So, the author had a goal to compare these two dimensions: the ideal constructed by scientists and the image reflected in the media. Attention was given also to ethical problems in civil service. The construction of the ideal portrait of civil servant, or civil service in general, was not among the primary state goals, so the majority of studied publications were published in 1926---1939. This was important for economists, lawyers, specialists of management, to mention just a few - A. Baliūnas, G. Galvanauskas, V. Graičiūnas, P. Lesauskis, S. Nacevičius, P. Raulinaitis, J. Šimkus, etc. Some of them had studied at western universities and were familiar with the newest managerial theories or were writing themselves on various questions including state administration or governance.